2013
DOI: 10.1016/j.bpj.2013.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Self-Organizing Chemoattractant Field Arising from Precise Pulse Induction of Its Breakdown Enzyme: A Single-Cell Level Analysis of PDE Expression in Dictyostelium

Abstract: The oscillation of chemoattractant cyclic AMP (cAMP) in Dictyostelium discoideum is a collective phenomenon that occurs when the basal level of extracellular cAMP exceeds a threshold and invokes cooperative mutual excitation of cAMP synthesis and secretion. For pulses to be relayed from cell to cell repetitively, secreted cAMP must be cleared and brought down to the subthreshold level. One of the main determinants of the oscillatory behavior is thus how much extracellular cAMP is degraded by extracellular phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…S1 and SI Materials and Methods). Collective cAMP oscillations occur spontaneously in cell populations continuously perfused with buffer solution at a moderate flow rate (1.5 mL/min), where extracellular cAMP breakdown by secreted phosphodiesterase (PDE) in vivo is effectively emulated by dilution (24,28). First, we tested the effect of adding cAMP in the perfusion flow (hereafter refer to as "exogenous cAMP"), which adds on top of endogenously synthesized and secreted cAMP present in the extracellular space.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 and SI Materials and Methods). Collective cAMP oscillations occur spontaneously in cell populations continuously perfused with buffer solution at a moderate flow rate (1.5 mL/min), where extracellular cAMP breakdown by secreted phosphodiesterase (PDE) in vivo is effectively emulated by dilution (24,28). First, we tested the effect of adding cAMP in the perfusion flow (hereafter refer to as "exogenous cAMP"), which adds on top of endogenously synthesized and secreted cAMP present in the extracellular space.…”
Section: Resultsmentioning
confidence: 99%
“…These oscillations are driven intracellularly without the need for clearing of extracellular cAMP-a feature in favor of the Fitzhugh-Nagumo-type scheme. For the population-level oscillations, in contrast, a strict dependency on extracellular cAMP clearing has been demonstrated by a null-mutant of extracellular phosphodiesterase that cannot oscillate unless it is cleared of extracellular cAMP by perfusion (28). It may be that different cAMP receptor forms (52) or receptor types (53) with different binding constants transduce FCD and non-FCD signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By hydrolyzing cAMP at the cell surface, mPDE lowers its local concentration and steepens the gradient; the negative cooperativity of the enzyme helps in this (Nanjundiah & Malchow, ). Masaki et al () have found that in the axenic strain Ax2, external cAMP pulses cause rapid transcription from the pdsA gene. If generally valid, the observation indicates that mPDE activity too rises in parallel with the cAMP signal, which would be another sign of its significance for chemotaxis.…”
Section: Aggregation Via Chemotaxis In D Discoideummentioning
confidence: 99%
“…By hydrolyzing cAMP at the cell surface, mPDE lowers its local concentration and steepens the gradient; the negative cooperativity of the enzyme helps in this (Nanjundiah & Malchow, 1975). Masaki et al (2013) have found that in the axenic strain Ax2, external cAMP pulses cause rapid transcription from the pdsA gene.…”
Section: Extracellular Phosphodiesterase Is Not Required For Chemotmentioning
confidence: 99%